Evaluating velocity and temperature fields for Ranque Hilsch vortex tube using numerical simulation - Al Saghir, Ahmad Mohammad (2021)
In this study, a three-dimensional numerical investigation is carried out to study the flow field inside a Ranque-Hilsch vortex tube (RHVT) model. Flow parameters such as velocity, temperature, and pressure are plotted at various locations inside the tube. The study reports the effect of cold mass fraction on the energy separation of vortex tube . The results show that the flow inside RHVT consists of a free vortex from r/R=0 to 0.9 and a force vortex from r/R=0.9 to 1 and that heat transfer occurs from the inner core to the periphery of the tube. Furthermore, it is observed that the minimum cold temperature and the maximum hot temperature are achieved at different mass fractions, 0.19 and 0.8, respectively.